Hydrosystems Engineering reliability assessment and risk analysis - Tung, Yeou-Kong (McGraw-Hill, 2006)
Failure of hydrosystems, such as dams, levees, storm sewers, or pollution control systems, pose threats to the public safety and health as well as potentially inflict enormous damages on properties and environments. Many failures of hydrosystems are mainly attributed by the existence of various uncertainties, including inherent natural randomness and the lack of complete understanding of involved geophysical processes. It is therefore essential to systematically quantify the degree of uncertainty for the problem in hand so that reliability assessment and risk-based design of hydrosystems can be made. The conventional approach of frequency analysis of heavy rainfalls or large floods consider only portion of the uncertainties involved in hydrosystem engineering problems. Over the past two decades or so, there has been a steady growth on the development and application of uncertainty analysis techniques in hydrosystems engineering and other disciplines. The aim of this book is to bring together these uncertainty analysis techniques in one book and to demonstrate their applications and limitations for a wide variety of hydrosystem engineering problems.